Tillage and crop establishment affects sustainability of South Asian rice-wheat system - Gathala, Mahesh K.; Ladha, J.K.; Kumar, Vivak; Saharawat, Yashpal S.; Kumar, Virender; Sharma, Paradeep Kumar; Sharma, Sheetal; Pathak, Himanshu (Wiley, 2011)
Rice (Oryza sativa L.)–wheat (Triticum aestivum L.) is the major cropping system occupying 13.5 million ha in the Indo‐Gangetic Plains of South Asia. Conventional‐tillage practices are resource and cost intensive. A 7‐yr study evaluated six treatments (T) involving three tillage methods and two rice establishment methods on crop yield, water productivity, and economic profitability in a rice–wheat rotation. Average rice yields in the conventional practice of puddling and transplanting without (T1) and with (T2) mid‐season alternate wetting‐drying were highest (7.81–8.10 Mg ha−1) and increased with time (0.26 Mg ha−1 yr−1) in T2. Compared to T1, rice yields in direct drill‐seeding with zero‐tillage averaged 16% lower on flat (T5) and 43% lower in raised beds (T3). Rice yield in raised beds (T3 and T4) decreased with time (0.14–0.45 Mg ha−1 yr−1). Conversely, wheat yielded 18% higher after zero compared to conventional‐tillage. Treatment 2, despite low soil matric potential during vegetative development, had higher water productivity with 25% less water use compared with T1 and 19% less compared with other treatments. Conventional‐tillage and crop establishment practices had higher net cash return in rice but in wheat it was higher with zero‐tillage. Overall, T2 and T5 had the highest net returns (∼1225US$) and T3 and T4 had the lowest (747–846 US$) in the rice–wheat system. Zero‐tillage on flat beds (T5), however, would conceivably be more sustainable than the conventional T2 in the long‐run. Yields of zero‐tillage with direct‐seeding of rice on flat beds (T5) must improve before adoption occurs.